A Constitutive Model Description of the In Vivo Material Properties of Lower Birth Canal Tissue During the First Stage of Labor - Tracy, Paige V (J Mech Behav Biomed Mater, 2017)
Remarkable changes must occur in the pelvic floor muscles and tissues comprising the birth canal to allow vaginal delivery. Despite these preparatory adaptations, approximately 13% of women who deliver vaginally for the first time (nulliparas) sustain tears near the origin of the pubovisceral muscle (PVM) which can result in pelvic organ prolapse later in life. To investigate why these tears occur, it is necessary to quantify the viscoelastic behavior of the term pregnant human birth canal. The goal of this study was to quantify the in vivo material properties of the human birth canal, in situ, during the first stage of labor and compare them to published animal data. The results show that pregnant human, ovine and squirrel monkey birth canal tissue can be characterized by the same set of constitutive relations; the interspecies differences were primarily explained by the long time constant, τ(2), with its values of 555 seconds, 1110 seconds, and 2777 seconds, respectively. Quantification of these viscoelastic properties should allow for improved accuracy of computer models aimed at understanding birth-related injuries.